Variation in population density of Apis mellifera L. on tangerine crop - Vargas, Yessica (2020)
The research was carried out in order to determine the variation in population density of Apis mellifera L. along blooming period of Satsuma Owari tangerine (Citrus unshiu Marc.), according to environmental factors at Huaral – Lima. Adults honey bee data were registered on 10 trees, three times a week, on schedules from 8:00 a.m. – 10:00 a.m., 1:00 p.m. – 3:00 p.m. and 3:00 p.m. – 5:00 p.m. on flower buds, opened flowers and withered flowers phases. Besides, aspects of adult bee behavior were registered. Low population values were registered on flower buds and withered flowers phases, while high values were registered on opened flowers phase by the presence of nectar. Higher densities of adult bees were registered at 11:00 a.m. – 1:00 p.m. and 3:00 p.m. – 5:00 p.m. schedules, because of good temperature and solar radiation conditions, while low values were registered on 8:00 a.m. – 10:00 a.m. schedule. The research indicates that tangerine compete against other fruit trees, respect to the visit of bees for harvest of pollen, nectar and pollination, on schedule from 11 a.m. forward on flowering period.